Source of SARS-CoV-2 infection: results from a series of 584,846 cases in France from October 2020 to August 2022 - Arthur Rakover; Simon Galmiche; Tiffany Charmet; Olivia Chény; Faïza Omar; Christophe David; Sophie Martin; Alexandra Mailles; Arnaud Fontanet (BMC, 2024)
Abstract Background We aimed to study the source of infection for recently SARS-CoV-2-infected individuals from October 2020 to August 2022 in France. Methods Participants from the nationwide ComCor case-control study who reported recent SARS-CoV-2 infection were asked to document the source and circumstances of their infection through an online questionnaire. Multivariable logistic regression was used to identify the factors associated with not identifying any source of infection. Results Among 584,846 adults with a recent SARS-CoV-2 infection in France, 46.9% identified the source of infection and an additional 22.6% suspected an event during which they might have become infected. Known and suspected sources of infection were household members (30.8%), extended family (15.6%), work colleagues (15.0%), friends (11.0%), and possibly multiple/other sources (27.6%). When the source of infection was known, was not a household member, and involved a unique contact (n = 69,788), characteristics associated with transmission events were indoors settings (91.6%), prolonged (> 15 min) encounters (50.5%), symptomatic source case (64.9%), and neither the source of infection nor the participant wearing a mask (82.2%). Male gender, older age, lower education, living alone, using public transportation, attending places of public recreation (bars, restaurants, nightclubs), public gatherings, and cultural events, and practicing indoor sports were all independently associated with not knowing the source of infection. Conclusion Two-thirds of infections were attributed to interactions with close relatives, friends, or work colleagues. Extra-household indoor encounters without masks were commonly reported and represented avoidable circumstances of infection. Trial registration ClinicalTrials.gov registration number: NCT04607941.